2021
DOI: 10.1051/e3sconf/202124203006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Solidity Ratio on the Small Wind Turbine Aerodynamics

Abstract: Increasing popularity of individualised electricity generation from wind by prosumers creates a strong demand for profitable and highly efficient small wind turbines. This paper investigates the influence of rotor blade solidity parameter on device efficiency in hope of determining its optimal value as a part of the development process of the GUST small wind turbine. The study involved experimental analysis in the wind tunnel and numerical simulations performed in QBlade software. Different solidities of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Contrary to the findings in Refs. [15,16,28,32] we did not find a significant decrease in the optimum tip-speed ratio with an increase in blade solidity. However, these previous studies have focused on larger wind turbines operating at higher tip-speed ratio, therefore the range and magnitude of blade solidity is significantly lower and the actual results can hardly be replicated to fast wind turbines.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Contrary to the findings in Refs. [15,16,28,32] we did not find a significant decrease in the optimum tip-speed ratio with an increase in blade solidity. However, these previous studies have focused on larger wind turbines operating at higher tip-speed ratio, therefore the range and magnitude of blade solidity is significantly lower and the actual results can hardly be replicated to fast wind turbines.…”
Section: Resultsmentioning
confidence: 52%
“…Another recent experimental study by Zawadzki et al in Ref. [28] reports other conclusions. They performed wind tunnel experiments with a 400 mm wind turbine equipped with blades with constant chord length.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…When the lift coefficient is good and the drag coefficient is low, the NACA 4418 airfoil exhibits suitability for applications in the construction of turbine blades [9]. CFD simulation techniques have also been utilized in earlier research to examine the performance of wind turbines, the choice of airfoil profiles, the impact of the number of blades being employed, and pitch angle variations [12][13][14][15][16][17]. Previous research has used the GIT technique to choose a quality mesh while also reducing time to ensure that the data obtained reaches the actual reading [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the increase of the power factor with the increase in the so-called rotor solidity as well as the increase in the number of blades. The simulation of this turbine was done using the Qblade program, where the work to improve the toughness of the rotor has a positive effect on the performance of the full and total energy [17]. To track the characteristics of the overall wind turbine (VAWT) structure, it is important that the design control, experimentally, reflects positively on the reality of wind turbines, so attention must be paid to studying aerodynamics significantly, particularly to the results, especially the measured torque and thus the wind tunnel are fully simulated from the turbine design to the analysis and interpretation of aerodynamics [18].…”
Section: Introductionmentioning
confidence: 99%